The Modern British Essayists - Lord Jeffrey - Jeffrey, Francis (Philadelphia : A. Hart, Late Carey & Hart, 1852)
Francis Jeffrey, a.k.a. Lord Jeffrey, was a Scottish judge and literary critic best known for his contributions to the Edinburgh review, which this text highlights. Mainly a general literature with literary biography.
Contributions to the Edinburgh review
Historical memoirs and works comprising 762 pages. Volume 6 in the series: The Modern British essayists. This one focusing on Lord Jeffrey [1852]. Slight foxing amongst several pages, does not obscure text.
Keywords: Rare books, Francis Jeffrey, Modern British Essayists, Lord Jeffrey, Contributions to the Edinburgh review